2020
DOI: 10.1177/0022146520902796
|View full text |Cite
|
Sign up to set email alerts
|

Race-Ethnicity, Social Roles, and Mental Health: A Research Update

Abstract: Social role involvement engenders sense of purpose and meaning to life, which sustains positive mental health. Racism within American society, however, results in experiences that disadvantage ethnoracial minorities, thus making it likely that social roles do not have universal remunerations. Using the Collaborative Psychiatric Epidemiology Surveys (N = 12,526), this study explores the association between role participation and psychological distress across nine ethnoracial groups. Results indicate that engagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…Fourth, we focus on the intersection of three important social roles. Race‐gender status is associated with alienation levels, access to valued social resources, and cultural meanings about the appropriate combination of social roles (Jackson, 1997; Jackson & Erving, 2020). Future research should incorporate whether other social roles (e.g., friend, church member, volunteer) complicates the patterns presented here as well as whether having a minor child in the home versus an adult child impacts the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we focus on the intersection of three important social roles. Race‐gender status is associated with alienation levels, access to valued social resources, and cultural meanings about the appropriate combination of social roles (Jackson, 1997; Jackson & Erving, 2020). Future research should incorporate whether other social roles (e.g., friend, church member, volunteer) complicates the patterns presented here as well as whether having a minor child in the home versus an adult child impacts the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mouzon et al (2016) did not find that levels of psychological distress among African Americans differed by marital or parental status after accounting for a host of covariates (e.g., age, gender, and socioeconomic status) though the combination of these roles may be more important for mental health. For instance, Jackson and Erving (2020) found that the spousal role among African Americans is not as consequential for mental health as other racial‐ethnic groups; however, marriage is beneficial to the mental health of African Americans when in combination with parenthood and employment. African American women have historically been gainfully employed at higher rates than white women (Collins & Moody, 2017), and employment is associated with increased independence, socioeconomic resources, and better health (Kostiainen, Martelin, Kestilä, Martikainen, & Koskinen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The findings presented here suggest that differences in the experience of work during the pandemic is both itself an important dimension of SES disparities in COVID-19 morbidity and mortality and a contributor to educational and racial-ethnic health inequalities. Thus, as with prepandemic health inequalities, occupations contribute to structurally racist health inequalities (Forman 2003; Jackson and Erving 2020; McCluney et al 2018) and educational health stratification (Chandola et al 2006; Elo 2009) during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior research on race-ethnicity, SES, and health, which documents health inequalities along these dimensions, although not for recent immigrants (Elo 2009; Williams, Lawrence, and Davis 2019; Zang and Kim 2021). Research on structural racism and health has linked work characteristics and employment to racial differences in stress, episodic memory, and self-related health (Forman 2003; Jackson and Erving 2020; McCluney et al 2018). Given educational, racial, and ethnic occupational segregation (Catanzarite 2000; Tomaskovic-Devey et al 2006), occupational inequalities in material rewards and exposure to health risks, in turn, contribute to SES, racial, and ethnic health disparities during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may be related to racial differences in participation and autonomy in a variety of settings (Jackson & Erving, 2020). In research and medical settings, there is evidence that Black and African American individuals may be less likely to participate in research than White individuals based on a lack of trust in the medical and research communities (Shavers et al, 2002).…”
Section: Introductionmentioning
confidence: 99%